Amniotic fluid neutrophil gelatinase‐associated lipocalin and L‐type fatty acid‐binding protein in predicting fetal inflammatory response syndrome. Issue 8 (30th May 2021) - Katsura, Daisuke; Tsuji, Shunichiro; Hayashi, Kaori; Tokoro, Shinsuke; Zen, Rika; Hoshiyama, Takako; Nakamura, Akiko; Kimura, Fuminori; Kita, Nobuyuki; Murakami, Takashi
Abstract: Aim: To analyze the effectiveness of amniotic fluid neutrophil gelatinase‐associated lipocalin and L‐type fatty acid‐binding protein as predictive factors for fetal inflammatory response syndrome. Methods: We classified single pregnancy cases into the fetal inflammatory response syndrome and nonfetal inflammatory response syndrome groups. We collected amniotic fluid at vaginal delivery and cesarean section and compared the patient characteristics, maternal white blood cell count, C‐reactive protein level, and amniotic fluid interleukin‐6; neutrophil gelatinase‐associated lipocalin; and L‐type fatty acid‐binding protein levels between the groups. We further analyzed the relationship between L‐type fatty acid‐binding protein levels and neonatal clinical outcomes. Results: We analyzed 129 pregnancies, of which 36 and 93 (27.9% and 72.1%, respectively) were classified into the fetal inflammatory response syndrome and nonfetal inflammatory response syndrome groups, respectively. We observed significant differences in the maternal white blood cell counts and amniotic fluid interleukin‐6 and neutrophil gelatinase‐associated lipocalin levels. On the multivariate analysis, the useful predictive factors were maternal white blood cell count and amniotic fluid interleukin‐6 and neutrophil gelatinase‐associated lipocalin levels. Furthermore, the level of L‐type fatty acid‐binding protein was significantly higher in the transient tachypnea of the newborn and postnatal respiratory support group than in the control group. Conclusions: The maternal white blood cell count and amniotic interleukin‐6 and neutrophil gelatinase‐associated lipocalin levels were effective predictors of fetal inflammatory response syndrome. Amniotic fluid L‐type fatty acid‐binding protein level was an effective predictor of neonatal respiratory support.